On the recyclability of glass fiber reinforced thermoset polymeric composites towards the sustainability of polymers' industry - Ribeiro, M.C.S. (2017)
Considering the added value of recycling solution assessed by an evaluation of flexural and compressive loading capacity of PC specimens modified with mechanically recycled GFRP wastes, as well as the inherent environmental and economic benefits, the incorporation of GFRP recyclates into PC materials has been revealed as a viable technological option for the sustainability of the GFRP polymers’ industry. Nevertheless, the recyclability of composite materials is complex and is sometimes seen as a key barrier to the adoption of these materials in some markets. One of the few successful applications, was developed by Reprocover, in Belgium, and it has been commercialized since 2011. In addition, the recently investigation line that was started and concerning the GFRP recyclates into PC materials also called the attention of Global Fiberglass SolutionsTM group. Even so, and although all the efforts that had been done on developing cost-effective recycling routes, GFRP wastes still remain mired by the scarceness of reliable outlet markets for the recyclates and clearly developed recycling paths between waste producers and potential consumers for the recyclates. However, it is foreseen that this scenario will change in the next few years as strong investments are being made in this field. The innovation in this field has just started, providing as this way a source of new opportunities.